Pengembangan Gagasan Inovatif untuk Pembelajaran IPS di Sekolah Dasar - Tsania, Aura Rizky; Gumilar, Dinda Amelia; Rahayu, Rina; Yosep, Zahra Audyna; Arifin, Muh Husen (Indo-MathEdu Intellectuals Journal, 2025)
This article aims to develop innovative ideas in Social Studies (IPS) learning in primary schools through a literature study that examines various research findings and current learning practices. This study was motivated by the continued strong use of conventional methods, low digital literacy, and limited use of technology in the classroom. The method used is content analysis of various relevant sources to identify trends and alternative learning strategies. The results of the study show that the application of the Project Based Learning (PjBL) model, the integration of local values and wisdom, and the use of digital media can increase learning motivation, social literacy, and 21st-century skills of primary school students. This study emphasises the importance of improving teachers' pedagogical competencies, developing a more contextual curriculum, and strengthening students' social character as implications of learning innovations that are in line with the principles of the Merdeka Curriculum